Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.669447
|View full text |Cite
|
Sign up to set email alerts
|

Fis Connects Two Sensory Pathways, Quorum Sensing and Surface Sensing, to Control Motility in Vibrio parahaemolyticus

Abstract: Factor for inversion stimulation is a global regulator that is highly expressed during exponential phase growth and undetectable in stationary phase growth. Quorum sensing (QS) is a global regulatory mechanism that controls gene expression in response to changes in cell density and growth phase. In Vibrio parahaemolyticus, a marine species and a significant human pathogen, the QS regulatory sRNAs, Qrr1 to Qrr5, are expressed during exponential growth and negatively regulate the high cell density QS master regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…The Δ cyaA and Δ cyaB mutants grew similar to wild type producing typical budding swarming cells as previously shown for this species ( Fig. 6B ) (4345). The WT, Δ cyaA and Δ cyaB swarming colonies were examined further to show that the swarming colony structural differences were not due to mutants forming.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The Δ cyaA and Δ cyaB mutants grew similar to wild type producing typical budding swarming cells as previously shown for this species ( Fig. 6B ) (4345). The WT, Δ cyaA and Δ cyaB swarming colonies were examined further to show that the swarming colony structural differences were not due to mutants forming.…”
Section: Resultssupporting
confidence: 80%
“…Biofilm assays were performed as previously described (39, 40, 57). Briefly, overnight cultures were used to inoculate strip wells in a 1:40 dilution in LBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that Qrr1-5 negatively regulate the high cell density quorum-sensing regulator OpaR , which is required for biofilm formation and acts as a repressor of swarming motility [ 15 , 33 ]. However, we found that the cytotoxicity of Caco-2 cells increased with increasing post-infection time, and Qrr5 was significantly upregulated at different post-infection time points compared to Qrr1 – 4 ( Figure 1 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Fis is a regulator that negatively regulates the expression of the quorum-sensing master regulator OpaR and inhibits capsule polysaccharide (CPS) and biofilm formation, implying that Fis plays a direct role in the quorum sensing, biofilm formation, and metabolism of V. parahaemolyticus . Interestingly, when Fis binds directly to the regulatory regions of Qrr genes, it acts as a positive regulator [ 15 ].…”
Section: Introductionmentioning
confidence: 99%